Optimization of Iron (Fe2+) Adsorption on Commercial Granular Activated Carbon in A Fixed-Bed Column - Sylvia, Novi; ., Meriatna; Hasfita, Fikri; Fardian, Nur (International Journal of Engineering and Technology, 2019)
Adsorption process can also establishes a mathematical relationship between the interaction process of variables and process optimization is essential in measuringÂ factors values to obtain maximum respons number.The adsorption of Fe from ground water was optimized by using the methodology of response surface based on design idea of Box-Behnken. Adsorption data was analyzed using isotherm models. The process was measured usingÂ continue experiments. Variables in the process were bed depths (7,5, 10 and 12,5 cm), time (20, 40 and 60 min), flow rate (6, 10 and 14 L/min). Regression analysis was used to analyze the value of models developed. The result of this research showed the number of 95,598 % from the variations in removal rate of efficiency respectively are applied to three processes which variables considered, that is, bed depths, time and flow rate. Therefore, the models used as well to predictÂ the interaction of the process variables. Optimization tests showed the optimum process conditions for the adsorption process occurred at bed depths 11,36 cm, time 55,61 min and flow rate 6 L/min. These were considered as optimum operating conditions. There are two isotherm equations which have been tested, those are Langmuir and Freundlich. The Equilibrium adsorption data can be optimized when formulated in Â the Langmuir isotherm model.Â Â